The role of interest in Islamic financial transactions - Samsuri, Nur Bahiyah Adibah; Yaakob, Fathiah; Mat, Nur Insyira; Wan Abdul Rahim, Wan Norsyazwanie; Mohd Rizal, Maisarah Izzah Hazwani; Zabidi, Nur Ain Amalin (2025)
In general terms, interest is the attainment of all benefits or the rejection of all potential harm. More specifically, benefit is the expression of pleasure or anything related to it, while harm is painful things or anything related to them. Interest is also a quality or condition suitable for establishing a law that brings good and prevents harm. The main objective of Sharia is to reject self-interest and accept self-interest. Introduction to self-interest. In the context of Islam, self-interest refers to the importance or benefit that takes priority in human life, in line with the main objective of Islamic Sharia, which is to achieve well-being in this world and the hereafter. It is an important principle in establishing laws that aim to protect five basic human needs: religion, life, reason, lineage, and wealth.